2009
DOI: 10.1007/s00467-008-1005-9
|View full text |Cite
|
Sign up to set email alerts
|

Membranous glomerulonephritis: treatment response and outcome in children

Abstract: The aim of this study was to characterize clinical features, treatment response, and outcome of idiopathic membranous glomerulonephritis (MGN) in a single-center cohort of children. A retrospective review of biopsy-proven idiopathic MGN in 12 children (mean age 11.9 years) was undertaken. Presentation was nephrotic syndrome (NS) (75%), hematuria/proteinuria (17%), and asymptomatic proteinuria (8%). Ten patients (83%) with NS and nephrotic range proteinuria (NRP) were treated with prednisone, and two patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…In most cases, patients were elderly men with continuous massive proteinuria, and the pathological stages were mainly identified as stage III or IV accompanied by renal dysfunction at disease onset, and the progression of tubulointerstitial lesions, as well as poor prognosis associated with FSGS (Wasserstein, 1997;Valentini et al, 2009;Ponticelli and Passerini, 2010b;Praga and Rojas-Rivera, 2012). In the present study, pathological stages were identified as stage I in 16 cases, stage II in 6 cases, and stage III in 1 case.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In most cases, patients were elderly men with continuous massive proteinuria, and the pathological stages were mainly identified as stage III or IV accompanied by renal dysfunction at disease onset, and the progression of tubulointerstitial lesions, as well as poor prognosis associated with FSGS (Wasserstein, 1997;Valentini et al, 2009;Ponticelli and Passerini, 2010b;Praga and Rojas-Rivera, 2012). In the present study, pathological stages were identified as stage I in 16 cases, stage II in 6 cases, and stage III in 1 case.…”
Section: Discussionsupporting
confidence: 45%
“…Data indicate that a third of IMN patients gradually progress to end-stage renal disease (Valentini et al, 2009), but the factors affecting prognosis are varied in literature. In most cases, patients were elderly men with continuous massive proteinuria, and the pathological stages were mainly identified as stage III or IV accompanied by renal dysfunction at disease onset, and the progression of tubulointerstitial lesions, as well as poor prognosis associated with FSGS (Wasserstein, 1997;Valentini et al, 2009;Ponticelli and Passerini, 2010b;Praga and Rojas-Rivera, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a pediatric population, there is always the added concern of inducing infertility, however the use of a limited course of low-dose cyclophosphamide can avoid cumulative doses that would be concerning for gonadal toxicity. One option that provides a relatively low exposure to cyclophosphamide (total dose of < 200 mg/kg) involves a 12 week regimen using daily cyclophosphamide (2 mg/kg/day) with alternate-day steroids and was used successfully in a small uncontrolled study [61]. Calcineurin inhibitors may also be effective but, based on experience in adults, they require 6–12 months of therapy with a slow taper to avoid relapse.…”
Section: Treatment Of Mnmentioning
confidence: 99%
“…301, 302, 303 This may also apply to other types of primary GN associated with severe nephrotic syndrome; the evidence base, however, is lacking. There have been no RCTs of prophylactic anticoagulation in IMN with nephrotic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…There have been no RCTs of prophylactic anticoagulation in IMN with nephrotic syndrome. 301, 302, 303 …”
Section: Introductionmentioning
confidence: 99%